Implementasi SMART Untuk Kelayakan Penerima Beasiswa KIP STMIK Palangkaraya: SMART Implementation for the Eligibility of KIP K STMIK Palangkaraya Scholarship Recipients - Rusdiana, Lili; Cahya Hardita, Veny; Elmayantie, Catharina; Lafito, Andi (Jurnal Sains Komputer dan Teknologi Informasi, 2025)
The selection of students receiving KIP (Smart Indonesian Cards) Lectures at STMIK Palangkaraya so far has been by surveying student data files based on school grades, family economy, and burdens borne by parents. In this selection, it was found difficult to determine the eligibility of students receiving KIP Lectures, namely selecting data manually. To facilitate the selection process, a decision-making system was built that could be used by student selection officers to help decide whether to get KIP Lectures at STMIK Palangkaraya. SMART method, which is a way of making decisions by calculating the weight of the criteria for each given alternative from the Student data file. The stages of the research carried out are the process of collecting criteria data, the process of weighting and normalization, the process of searching for utility values, and the process of ranking. Data collection techniques used are interviews, documentation, and literature. Comparison of the results of calculations between systems using the SMART method and manual processes results in the same results. However, there were 2 results that were not feasible because the parents' income factor was too large so that the KIP recipient candidates did not deserve to get the KIP K scholarship.